Use of biochemical and protein profiles of seminal plasma to prediction of semen quality and fertility in stallions - Stelletta, C. (2022)
The identification of various substances in seminal plasma has opened the way to study their functionality. It was aimed to identify the electrophoretic protein profile (EPP) and biochemical parameters (BP) of seminal plasma (SP) as predictors of semen quality and fertility in stallion. Forty-six ejaculates from 7 fertile stallions, aged between 6-26 years, were collected from May to July and 117 mares were used to obtain fertility data. For each ejaculate, volume, sperm motility, concentration were determined and seminal plasma samples were collected to perform one-dimensional electrophoresis and biochemical profiling. Following the estrus detection, mares were inseminated with fresh sperm. Pregnancy rates and foal rates were recorded. The concentration of 15-18 kDa molecular weight (MW) proteins has shown a positive correlation with sperm concentration and foal rate. Besides, a strong positive correlation was found between sperm concentration and 23-28 kDa MW proteins (r=0.77). The volume of 19-22 kDa MW proteins was negatively correlated with pregnancy and foal rate. Similarly, the volume of high MW proteins (173-385 kDa) correlated negatively with sperm motility and foal rate. Apart from the protein profile, while Magnesium and Glucose levels were negatively correlated with sperm quality and foal rate, Cholesterol level was a positive indicator of the quality of semen as well as the foaling rate. Moreover, the total protein level was correlated negatively with the sperm concentration whereas triglyceride was correlated positively. In conclusion, EPP and BP of seminal plasma are valuable clinical tools as predictors of fertility and semen quality in the stallion.